(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the importance and effectiveness of online resources in developing linguopragmatic competence. The article analyzes how modern information and communication technologies and Internet resources can improve the language learning process and help students improve their ability to use speech correctly in a sociocultural context. The article discusses in detail the potential of online learning platforms, MOOC courses, video tutorials and podcasts, interactive simulators, role-playing games, and scientific resources in the formation of linguopragmatic competence. The article emphasizes that, unlike traditional textbooks, digital resources provide real communicative situations, help to understand the cultural context, and create an opportunity to correct students’ pragmatic errors. The results of the study show that regular use of online resources significantly improves linguopragmatic skills and prepares language learners for real-life communicative situations.